2006
DOI: 10.1158/1078-0432.ccr-06-0592
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide and Substance P Regulate the Intestinal Radiation Response

Abstract: Purpose: Intestinal toxicity is important in the therapeutic use of radiation as well as in nontherapeutic radiation exposure scenarios. Enteric sensory nerves are critical for mucosal homeostasis and for an appropriate response to injury. This study assessed the role of the two major neuropeptides released by sensory nerves, calcitonin gene-related peptide (CGRP) and substance P, in the intestinal radiation response. Experimental Design: Male rats received full-length CGRP, CGRP antagonist (CGRP 8-37 ), a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Many pharmacological and genetic models also showed that the relationship cannot be explained simply by consequential late effects, for example, mast cell deficient rats, sensory nerve-ablated rats, and TGF-beta heterozygous rats all show dissociations between early and delayed injury 2629 , i.e. , all have exacerbated epithelial injury, but reduced levels of intestinal fibrosis.…”
Section: Consequential Late Effectsmentioning
confidence: 99%
“…Many pharmacological and genetic models also showed that the relationship cannot be explained simply by consequential late effects, for example, mast cell deficient rats, sensory nerve-ablated rats, and TGF-beta heterozygous rats all show dissociations between early and delayed injury 2629 , i.e. , all have exacerbated epithelial injury, but reduced levels of intestinal fibrosis.…”
Section: Consequential Late Effectsmentioning
confidence: 99%
“…Interestingly, both downregulation of TNF- α and upregulation of IGF-1 are associated with reduced normal tissue radiation injury [112, 113]. In line with this evidence, CGRP has been shown to protect in a rat model of radiation enteropathy [114]. Its role in RIHD has not yet been studied extensively.…”
Section: Mast Cell Interactionsmentioning
confidence: 99%
“…The roles of the two sensory neuropeptides CGRP and substance P have been studied extensively in a rat model of radiation enteropathy [135]. Small intestine mRNA levels of both neuropeptides were upregulated after local irradiation.…”
Section: Cardiac Sensory Nervous Systemmentioning
confidence: 99%
“…Administration of CGRP ameliorated radiation-induced intestine injury in rats, while a CGRP antagonist exacerbated injury, suggesting that CGRP played a protective role. Opposing results were obtained from the administration of substance P and a substance P receptor antagonist, suggesting that substance P played an aggravating role in intestinal radiation injury [135]. Considering the mast cell involvement in radiation-induced upregulation of CGRP in experimental RIHD and the known protective roles of CGRP in experimental radiation enteropathy and in myocardial injury from other causes, the role of this neuropeptide in RIHD deserves further investigation.…”
Section: Cardiac Sensory Nervous Systemmentioning
confidence: 99%